EFEKTIVITAS PELAYANAN PUBLIK DAN GOOD GOVERNANCE: STUDI KRITIS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BOLAANG MONGONDOW - Tesri Paputungan; Darmawati Darmawati; Kingdom Makkulawuzar (Al-Mizan (e-Journal), 2026)
This study examines the effectiveness of public services at the Population and Civil Registration Office (Disdukcapil) of Bolaang Mongondow Regency in realizing good governance, with a particular focus on accountability, transparency, and public participation as the three principal indicators. Employing a qualitative juridical approach through in-depth interviews with nine informants comprising four government officials and five community members and analyzed through the lens of Soerjono Soekanto's legal effectiveness theory, the research reveals a significant structural gap between institutional claims and the lived experience of service recipients. Accountability has been operationalized through Service Level Agreements and systematic Standard Operating Procedures, yielding measurable improvements in compliance ratings from the Ombudsman. However, transparency remains critically deficient: despite multi-channel information dissemination through websites, social media, and village coordination networks, not a single community informant reported receiving procedural information through those channels prior to their visit to the office. Participation is similarly nominal formal complaint mechanisms including SP4N-LAPOR and suggestion boxes exist on paper, yet all community respondents stated they had never been involved in service evaluation or consulted on service standards. Three structural inhibitors are identified: inconsistency in law enforcement apparatus behavior, inadequate physical and technological infrastructure including a single-unit ID card printer and unstable internet connectivity, and deeply entrenched cultural factors manifested in the persistent use of brokers (calo) and low civil registration compliance particularly in marriage recording. These findings contribute an analytical framework for evaluating local government public service effectiveness within decentralized governance contexts in Indonesia.